No effect of attentional modulation by spatial cueing in a masked numerical priming paradigm using continuous flash suppression (CFS) - Juliane Handschack; Marcus Rothkirch; Philipp Sterzer; Guido Hesselmann (PeerJ, 2023)
One notion emerging from studies on unconscious visual processing is that different “blinding techniques” seem to suppress the conscious perception of stimuli at different levels of the neurocognitive architecture. However, even when only the results from a single suppression method are compared, the picture of the scope and limits of unconscious visual processing remains strikingly heterogeneous, as in the case of continuous flash suppression (CFS). To resolve this issue, it has been suggested that high-level semantic processing under CFS is facilitated whenever interocular suppression is attenuated by the removal of visuospatial attention. In this behavioral study, we aimed to further investigate this “CFS-attenuation-by-inattention” hypothesis in a numerical priming study using spatial cueing. Participants performed a number comparison task on a visible target number (“compare number to five”). Prime-target pairs were either congruent (both numbers smaller, or both larger than five) or incongruent. Based on the “CFS-attenuation-by-inattention” hypothesis, we predicted that reaction times (RTs) for congruent prime-target pairs should be faster than for incongruent ones, but only when the prime was presented at the uncued location. In the invisible condition, we observed no priming effects and thus no evidence in support of the “CFS-attenuation-by-inattention” hypothesis. In the visible condition, we found an inverse effect of prime-target congruency. Our results agree with the notion that the representation of CF-suppressed stimuli is fractionated, and limited to their basic, elemental features, thus precluding semantic processing.